Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $(a_n), (b_n)$ are two sequences of real numbers so that $(a_n)\rightarrow a,\,\,(b_n)\rightarrow b$ with $a, b\in \mathbb{R}^+$. How to prove that $a_n^{b_n}\rightarrow a^b$ ?

share|improve this question
add comment

3 Answers

up vote 4 down vote accepted

Since $a_n\to a$ and $a>0$ by assumption, we have $a_n>0$ for $n\geq N$ for some sufficiently large positive integer $N$. So we can just consider $\log a_n$ for $n\geq N$. Note that $\log$ is a continuous function, we have $$\lim_{n\to\infty}(\log a_n)=\log(\lim_{n\to\infty} a_n)=\log a.$$ Therefore, we have $$\log\Big(\lim_{n\to\infty} a_n^{b_n}\Big)=\lim_{n\to\infty}(\log a_n^{b_n})=\lim_{n\to\infty}(b_n\log a_n)=(\lim_{n\to\infty}b_n)(\lim_{n\to\infty}\log a_n)=b\log a=\log a^b,$$ which implies that (by taking exponential on both sides) $$\lim_{n\to\infty} a_n^{b_n}=a^b$$ as required.

share|improve this answer
add comment

The function $f(x,y) = x^y = e^{y \ln x}$ is continuous on $\mathbb{R}_+ \times \mathbb{R}$, hence if $(a_n,b_n) \to (a,b)$ (with $a_n, a >0$, of course), then $a_n^{b_n} = f(a_n,b_n) \to f(a,b) = a^b$.

share|improve this answer
add comment

Note: The statement doesn't require $b > 0$. We don't assume it here.

If we take the continuity of $\ln$ and $\exp$ for granted, the problem essentially boils down to showing $b_n x_n \to bx$ where $x_n = \ln a_n, x = \ln a$ since $a_n^{b_n} = e^{b_n x_n}$. This is what the work in the first proof below goes toward (the "add-and-subtract $b_n \ln a_n$" trick comes up elsewhere too). But if you can use $b_n \to b \text{ and } x_n \to x \implies b_n x_n \to bx$ then the proof simplifies to the second one below.

Proof: Given $\varepsilon > 0$, there exist $K_1, K_2 \in \mathbb{N}$ such that for $n \in \mathbb{N}$ we have $n > K_1 \implies |\ln a_n - \ln a| < \frac{\varepsilon}{2(|b|+1)}$ (since $a_n \to a \in \mathbb{R}^+ \implies \ln a_n \to \ln a$ by continuity of $\ln$ on $\mathbb{R}^+$) and $n > K_2 \implies |b_n - b| < \min(\frac{\varepsilon}{2 (|\ln a| + 1)},1)$ (by hypothesis). Let $K = \max(K_1, K_2)$. Then $$\begin{eqnarray} n > K \implies |b_n \ln a_n - b \ln a| &=& |b_n \ln a_n - b_n \ln a + b_n \ln a - b \ln a|\\ &\leq& |b_n \ln a_n - b_n \ln a| + |b_n \ln a - b \ln a|\\ &=& |b_n|\,|\ln a_n - \ln a| + |b_n - b|\,|\ln a|\\ &<& (|b| + 1)\,\frac{\varepsilon}{2(|b|+1)} + \frac{\varepsilon}{2 (|\ln a|+1)}\,|\ln a|\\ &<& \varepsilon \end{eqnarray}$$ so $b_n \ln a_n \to b \ln a \in \mathbb{R}$ by definition. But $x \mapsto e^x$ is continuous on $\mathbb{R}$, hence $a_n^{b_n} = e^{b_n \ln a_n} \to e^{b \ln a} = a^b$.

As mentioned at the top, using the theorem on the limit of a product gives this:

Short proof: $$\begin{eqnarray} a^b &=& \exp\left[b \ln a\right]\\ &=& \exp\left[\left(\lim_{n \to \infty} b_n\right)\left(\ln \lim_{n \to \infty} a_n\right)\right] &\text{ assumption}&\\ &=& \exp\left[\left(\lim_{n \to \infty} b_n\right)\left(\lim_{n \to \infty} \ln a_n\right)\right] &\text{ continuity of }\ln\text{ at }\lim_{n \to \infty}a_n = a \in \mathbb{R}^+&\\ &=& \exp\left[\lim_{n \to \infty} b_n \ln a_n\right] &\text{ product of limits }\longrightarrow\text{ limit of product}&\\ &=& \lim_{n \to \infty} e^{b_n \ln a_n} &\text{ continuity of }\exp\text{ at }\lim_{n \to \infty}b_n \ln a_n = b \ln a \in \mathbb{R}&\\ &=& \lim_{n \to \infty} a_n^{b_n} \end{eqnarray}$$

All the work and $\varepsilon$'s are still there, but now they're hidden in the theorems we used.

share|improve this answer
    
This seems to yield only that $a_n^b\to a^b$. –  Did Jul 6 '12 at 6:30
    
Yes, there are some steps for him to fill in. (Exercise for the reader!) I wanted to stick with functions of one variable. –  Vandermonde Jul 6 '12 at 6:32
    
And now as show that $a_n ^{b_n}\rightarrow a^b$ –  Roiner Segura Cubero Jul 6 '12 at 6:39
    
I am all for leaving some steps to fill in but this is not so here. In fact such a hint is dangerously close to suggesting a wrong answer (first step being that $a_n^b\to a^b$, second step being that $a^{b_n}\to a^b$, then what?). –  Did Jul 6 '12 at 6:41
    
I fleshed out the answer (this is what I meant by using continuity). In retrospect, though, I see your point. Thanks for getting me to improve this. –  Vandermonde Jul 6 '12 at 7:53
show 1 more comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.